PERAN KUALITAS RELASIONAL SEBAGAI ANTESEDEN NIAT PEMBELIAN KEMBALI WISMAN PADA MAKANAN TRADISIONAL BALI - I Putu Utama; I Nyoman Rinala (JURNAL BISNIS HOSPITALITI, 2017)
This research is motivated by business issues that show menus in star hotels in Bali are generally dominated by foreign food, while Balinese traditional food is only 5% of menu composition. One strategy to increase the popularity of Balinese traditional food can be done by increasing the loyalty of foreign tourists based on the repurchase intention. This study aims to increase the repurchase intention offoreign tourists on Balinese traditional food in star hotels using theory of relationship marketing, theory of reasoned action and theory of expectationsdisconfirmation. Based on the concept of relationship marketing can be identified two variables of relationship quality, namely satisfaction and trust that can be antecedent of repurchase intention. In the research model it is stated that trust can act as an intervening variable on the association of satisfaction and repurchase intention. The purposive sampling method was conducted on 100 foreign tourists who bought Balinese traditional food at four star hotel in Bali in 2017, and data were analyzed by SEM. The results showed satisfaction does not significantly affect the repurchase intention, but satisfaction has a significant effect on trust and trust significantly affect the repurchase intention. Thus, the trust of foreign tourists plays an important role in determining the repurchase intention on Balinese traditional food in star hotels. The results of this study have implications for studies related to relationship marketing and the practical implications for the restaurant business-of star hotel.